PENDAMPINGAN ASSESSMENT PEMBELAJARAN TERINTEGRASI DI PONDOK PESANTREN BAHRUL MAGHFIROH KOTA MALANG - Ibnu Mujib; Jazuli Jazuli; Riyanto Riyanto; Susandi Susandi; Trio Ageng Prayitno (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2021)
This assessment is carried out to evaluate the learning process by emphasizing aspects of the integrated curriculum developed at the Bahrul Maghfiroh Islamic Boarding School. This process, which at every stage of its history has always undergone changes and dynamic cycles, must receive serious attention. The issue of curriculum since the implementation of the merger between the boarding school curriculum and the general school curriculum to this day is still a long debate, especially how the pesantren curriculum, which was originally oriented to ansih Islamic boarding school, must accommodate the general curriculum which is actually far from the experience expected by previous pesantren. This assessment is carried out with a grounded approach by conducting sufficient interviews, distributing questionnaires, and tracking school or boarding documents and followed by focus group discussions (FGD). At the implementation level, the curriculum merger effort at the Bahrul Maghfiroh Islamic Boarding School in Malang City is still limited to improving the school or class schedule, which means that on the improvement side at the level of material or certain fields of study, it is still in the process of improving and discussing discussions by coordinating continuously and thoroughly. In addition, at this stage the supporting laboratories are almost 70 percent completed to adjust to global needs which will be used and utilized by students in the future. The fields of agriculture, animal husbandry, and student entrepreneurship, and small industrial industries, in the future will become laboratories, not only for the sake of an integrated curriculum but also in general the vision of this pesantren, including strengthening the capacity of relevant learning media, but also upgrading Islamic boarding school human resources, so that they are able to synergize with digital speed which is the key in the era of the industrial revolution 4.0, currently the Bahrul Maghfiroh Islamic Boarding School is preparing